Serum neopterin levels in patients with chronic hepatitis B - Kalkan, A; Mehmet, O; Akbulut, H (Natl Inst Infectious Diseases, 2005)
The aim of this study was to determine the neopterin levels and peripheral blood lymphocyte subgroups in HBeAg-positive and -negative chronic hepatitis B patients. A total of 89 patients were included in the study. The mean serum neopterin level of patients with chronic hepatitis B was significantly higher than that of the control group. In HBeAg-positive chronic hepatitis B patients, the mean serum neopterin level was significantly higher than that of anti-HBeAb-positive patients. There was no significant correlation between the serum neopterin levels and alanine aminotransferase and HBV-DNA levels in HBeAg-positive chronic hepatitis B patients. There were no significant differences between the control subjects and patients with HBeAg-positive or anti-HBeAb-positive hepatitis in terms of the percentage of peripheral blood CD4(+) or CD8(+) or the ratio of CD4(+)/CD8(+) lymphocytes. Our results suggest an association between elevated neopterin concentrations and HBeAg-positivity in patients with chronic hepatitis B. However, there appears to be no association between the neopterin levels and either hepatocyte damage or viral replication status.
Keywords: Interferon-Alpha; Infection